PERAN PENDAMPINGAN KEPALA SEKOLAH DALAM MENINGKATKAN KUALITAS PEMBELAJARAN MELALUI KOMUNITAS BELAJAR DI SD NEGERI LEYANGAN - Riska, Riska Bhinita Sari; Sri Muji; Ayu Rosydina; Soedjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The government through the Ministry of Education, Culture, Research and Technology has implemented the Independent Curriculum for kindergarten, elementary, junior high, vocational and high school levels. One of the components needed for the successful implementation of the independent curriculum is the availability of competent educators. Improving student learning outcomes depends on the competence of educators, so a Principal must be able to facilitate improving educator competence. In an effort to improve the quality of education, the Ministry of Education, Culture, Research and Technology encourages educational units and educators to learn and share with each other through learning communities supported by the Independent Teaching Platform (PMM) and various other resources. Learning communities are considered one of the strategies for improving the competence of educators. This study aims to examine the Role of Principal Assistance in Improving the Quality of Learning through Learning Communities at SDN Leyangan. The author will use a descriptive research method through a qualitative approach. Data collection techniques are carried out by triangulation (observation, interviews, and documentation).